Comportamiento y actividad reproductora de los machos de Copris incertus Say (Coleoptera Scarabaeidae: Scarabaeinae) - Cruz R, Magdalena; Huerta, Carmen (Instituto de Ecología, A.C., 1998)
Copris incertus is a burrowing dung beetle whose female construct the nest which she tends until the brood emerges. In this paper we describe the modifications which the male reproductive system undergoes from its emergence and during the nesting process. We primarily considered the testicular and accessory glands (mesadenes) activities. Young individuáis have minimal testicular and glandular reservoir volumes and the spermatogenic and glandular activities are reduced. When the individuáis matures, the volume as well as the testicular and glandular activities notably increase. In oíd individuáis, we observe a testicular degenerativa process, but the secretion activity of the accessory glands is maintained due to the continuous secretion accumulation in the reservoir.